Emerging schooling landscapes in England: How primary system leaders are responding to new school groupings. (May 2019) - Simkins, Tim; Coldron, John; Crawford, Megan; Maxwell, Bronwen
In England the balance of responsibilities between national and local government for the governance of education is changing. Relationships between schools are shifting and new structures, groups and alliances are being created in response to national policy. The article is part of a project to understand how the new local education landscapes are emerging. Primary schools are relatively reluctant to embrace key aspects of national policy. We analysed interviews with primary system leaders in three contrasting local authorities to find out how they were responding, and why, and the nature of the groups they wanted to join, create or cooperate with. We identify concerns, interests and motivations that conflict with key aspects of national policy. In the process, we supplement earlier contributions as to how school groupings might usefully be categorised.